Implementation of a Sales Dashboard Using Metabase for Attendance Analysis and Sales Payroll Systems (Case Study: PT. Fiyansa) - Galeh Ariya Irwana; Rizqi Putri Nourma Budiarti (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2025)
In an effort to adopt digital technology, PT. Fiyansa has developed an Android application to monitor sales activities. However, the data generated by this application remains difficult to analyze regarding attendance and is insufficient for supporting decision-making. The primary factor causing this issue is the lack of adequate visualization. To address this problem, this research develops a dashboard to visualize attendance analysis and the payroll system. This dashboard generates visualizations categorized into three groups: attendance summary, sales performance analysis, and sales payroll. The attendance summary category consists of six visualizations, the sales performance analysis category comprises nine visualizations, and the sales payroll category includes three visualizations: payroll details, the three salespeople with the lowest salaries, and the three salespeople with the highest salaries. The results obtained from the dashboard analysis indicate that the level of sales salaries is significantly influenced by work attendance. This is evidenced by the analysis showing that salespeople with the highest salaries tend to have high attendance rates and a low frequency of lateness.